2022
DOI: 10.1177/23969415221077652
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of immediate retrieval and spaced retrieval to word learning in preschoolers with developmental language disorder

Abstract: Background and Aims Children with developmental language disorder (DLD) benefit from word learning procedures that include a mix of immediate retrieval and spaced retrieval trials. In this study, we examine the relative contribution of these two types of retrieval. Methods We examine data from Haebig et al. (2019) in their study that compared an immediate retrieval condition and a condition of spaced retrieval that also included immediate retrieval trials. Participants were 4- and 5-year old children with DLD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As such, domain-general tasks, like the cross-situational word learning paradigm, have been used to study developmental language disorder, apraxia of speech, aphasia, and late talking (Ahufinger et al, 2021 ; McGregor et al, 2022 ; Peñaloza et al, 2017 ). Moreover, several domain-general theory principles (e.g., spaced and variable learning) have been effectively applied to intervention work in clinical research settings (Desmottes et al, 2017 ; Haebig et al, 2019 ; Leonard et al, 2021 , 2022 ; Levlin et al, 2022 ; Plante et al, 2014 ). Why did SLPs nonetheless demonstrate similar alignment with the other participant groups?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, domain-general tasks, like the cross-situational word learning paradigm, have been used to study developmental language disorder, apraxia of speech, aphasia, and late talking (Ahufinger et al, 2021 ; McGregor et al, 2022 ; Peñaloza et al, 2017 ). Moreover, several domain-general theory principles (e.g., spaced and variable learning) have been effectively applied to intervention work in clinical research settings (Desmottes et al, 2017 ; Haebig et al, 2019 ; Leonard et al, 2021 , 2022 ; Levlin et al, 2022 ; Plante et al, 2014 ). Why did SLPs nonetheless demonstrate similar alignment with the other participant groups?…”
Section: Discussionmentioning
confidence: 99%
“…For instance, parents use pointing and eye-gaze in real-world settings, which has been linked to better language outcomes in children (e.g., Cartmill et al, 2010 ). Spaced schedules and variable contexts benefit learning in classrooms and clinical settings (e.g., Leonard et al, 2021 , 2022 ; Sobel et al, 2011 ). Finally, cross-cultural studies have shown that children acquire language from overheard speech in their environment (e.g., Shneidman & Goldin-Meadow, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this finding is that the frequency of retrieval attempts was increased, but not the spacing between learning and retrieval practice; that is, children engaged in retrieval practice immediately after hearing the novel words and not at a delay. Prior work has demonstrated that spacing out retrieval opportunities improves retention in comparison to providing immediate retrieval practice (Karpicke and Roediger, 2007;Haebig et al, 2019;Leonard and Deevy, 2020;Leonard et al, 2021Leonard et al, , 2022. Spacing out retrieval practice in time might have engaged the retrieval processes necessary to successfully retrieve the words at test.…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval practice should also be embedded in laboratory-based tasks (e.g., paired-associates task) and organic learning environments (e.g., preschool classrooms, parent-child dyads) to determine how the implementation of retrieval practice influences memory performance. Finally, this work should be conducted in a broad age and language ability range to account for developmental differences in retrieval practice effects (see Haebig et al, 2019;Leonard and Deevy, 2020;Leonard et al, 2021Leonard et al, , 2022 for work on retrieval practice in children with developmental language disorder). These endeavors will contribute to theoretical accounts that can explain developmental differences in retrieval practice effects.…”
Section: Discussionmentioning
confidence: 99%